1911
DOI: 10.1007/bf02793738
|View full text |Cite
|
Sign up to set email alerts
|

Über Darminvaginationen

Abstract: Kritik der geltenden Lehre yon der Invaginatio ,,ileocoecalis" und der iiblichen Nomenklatur; nebst kasuistischen BeitrSgen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1928
1928
1948
1948

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…T h e condition in Germany is known as ' the intestinal stenosis of Garre ' and several of his pupils published other examples of the same stricture and described them at length. Meyer (1905) and Matti (1911) made extensive reviews of the reported cases and investigated the effect of strangulation on the different layers of the intestinal wall.…”
Section: Historicalmentioning
confidence: 99%
“…T h e condition in Germany is known as ' the intestinal stenosis of Garre ' and several of his pupils published other examples of the same stricture and described them at length. Meyer (1905) and Matti (1911) made extensive reviews of the reported cases and investigated the effect of strangulation on the different layers of the intestinal wall.…”
Section: Historicalmentioning
confidence: 99%